Allelopathic effect of some aqueous plant extracts and pesticides on germination and seedling vigor of barley Hordeum vulgare L - Ahsyee, Ramadan; Abu Zakhar, Farhat; Marqab, Saleh (Journal of Pure & Applied Sciences, 2021)
This study was conducted in the laboratory of the Department of Botany, College of Science / Zintan University in 2020, in order to study the effect of aqueous extracts on the germination and seedling strength of barley plant, where a complete random analysis (CRD) was used with three replicates and one factor and the extracts are (T1 wormwood extract) Artemisia herba- alba (T2 Neem) Azadirachta indica (T3 Mint) Mentha varidis (T4 Eucalyptus) Eucalyptus woodwardii (T5 Capers) Spinosa capparis (T6 Artemisa)  Artemisa campestris (T7 Thyme) Thymus capitatus (T8 Rumba) peganum Harmala (T9 control) (T10 pesticide).  The results showed that the treatment of T6 extract led to a relative increase in germination that reached 58% and gave the highest rate of germination 2.5 seeds/day, while T2 extract gave the highest mean root length of 8.43 Cm and the average dry weight of the root 5 grams, as well as the highest average length of the feather.